Analisis PASTEL & SWOTPemanfaatan Teknologi Pumped Storage Hydropower Untuk Meningkatan Penetrasi Energi Terbarukan Di Indonesia - Mujammil Asdhiyoga Rahmanta (Proklamasi 45 University, 2022)
Renewable energy (RE) power plants can reduce the use of fossil fuel power plants that damage the environment related to CO2 emissions. Solar power centers and wind/wind power plants (PLTB) have intermittent characteristics related to their performance which is strongly influenced by environmental conditions such as fluctuations in solar radiation & wind speed. This creates problems in the stability & reliability of the electricity system so that its utilization is not optimal. Pumped storage hydropower (PSH) is a renewable energy-based technology that can store excess energy production in the electricity system at low load conditions to be distributed when the system is in peak load conditions. This study aims to determine the use of PSH concerning increasing the penetration of RE generators in the electricity system. Pastel & SWOT (Strength Weakness Opportunity Threat) analysis methods were used in this study. From the results of the discussion & discussion, it was found that PSH technology can support the penetration of RE power plants in Indonesia, especially PLTB & PLTS because it can eliminate the intermittency nature of these plants in the electricity system. In addition, PSH is also a mature energy storage medium on a large & economical scale, making it suitable for application in large & complex electrical systems. The strength of PSH is its mature technology, especially from the aspect of its large and economical capacity. The weakness of PSH is related to its utilization depending on the location due to the need for the area to have sufficient water potential with hilly natural conditions (their elevation), and relatively large land. The opportunity offered by PSH is that Indonesia has many areas that have the potential to be developed into PSH. In addition, the use of PSH can reduce the cost of production and increase the penetration of PLTS & PLTB. The threat of PSH is the trend of decreasing storage costs & increasing battery performance.